An in vivo Calcium Imaging Approach for the Identification of Cell-Type Specific Patterns in the Developing Cortex - Che, Alicia; De Marco García, Natalia V. (Frontiers in Neural Circuits, 2021)
Neuronal activity profoundly shapes the maturation of developing neurons. However, technical limitations have hampered the ability to capture the progression of activity patterns in genetically-defined neuronal populations. This task is specially daunting given the substantial diversity of pyramidal cells and interneurons in the neocortex. A hallmark in the development of this neuronal diversity is the participation in network activity that regulates circuit assembly. Here, we describe detailed methodology on imaging neuronal cohorts longitudinally throughout postnatal stages in the mouse somatosensory cortex. To capture neuronal activity, we expressed the genetically encoded calcium sensor GCaMP6s in three distinct interneuron populations, the 5HT3aR-expressing layer 1 (L1) interneurons, SST interneurons and VIP interneurons. We performed cranial window surgeries as early as postnatal day (P) 5 and imaged the same cohort of neurons in un-anaesthetized mice from P6 to P36. This longitudinal two-photon imaging preparation allows the activity of single neurons to be tracked throughout the developmental process and plasticity changes induced by sensory experience or learning, opening up avenues of research to answer fundamental questions in neural development in vivo.